Emerging role of artificial intelligence in product recommendation - Somani, Pritesh (Review of Artificial Intelligence in Education, 2023)
This short paper deals with the role of Artificial Intelligence in recommending the right set of products to customers especially for the E-Commerce websites. This paper highlights different product recommendation strategies used by business organizations at the same time the challenges faced by them in effective implementation of product recommendation along with the jargons associated with use of product recommendation. It also provides further insights on the actual working methodology behind recommending correct set of products to customers. A few Case studies on best possible use of Artificial Intelligence by different E-Commerce organizations is also presented towards better understanding of recommendations.